The impact of technology CSFs on customer satisfaction and the role of trust: an empirical study of the banks in Malaysia - Jan, Muhammad Tahir; Abdullah, Kalthom (Emerald Group Publishing Limited, 2014)
Purpose – The purpose of this paper is to identify and test technology-related critical success factors (CSFs) and its impact on trust and customer satisfaction. Design/methodology/approach – This paper analyses the causal relationship that exists between technology CSFs and customer satisfaction. It also investigates the mediating role of trust between these two. For this purpose data were collected quantitatively from 349 employees working in different banks, through self-administered questionnaire. The data analysis was conducted using SPSS and AMOS software. Factor analysis was performed to extract and decide on the number of factors underlying the measured variables of interest. Structural equation modelling was then used to examine the variables and the fitness of proposed model. Findings – The result revealed that technology CSFs positively affect customer satisfaction. Also, trust partially mediates the relationship between technology CSFs and customer satisfaction. A significant positive impact of technology CSFs on trust, and trust on customer satisfaction have also been obtained. Practical implications – The significant influence that technology CSFs have on customer satisfaction and trust shows that technology-related CSFs are inevitable for the success of customer relationship management (CRM) in financial services industry, particularly banks. Policy makers of service industry in general and financial service industry in particular may benefit from the findings of this study. Originality/value – Despite the plethora of research on CSFs for CRM, very limited attention has been given to testing and validating the identified CSFs. Negligible research has been conducted to investigate trust as a mediating variable in the relationship between technology CSFs and customer satisfaction. This paper, therefore, offers valuable insight into technology-related CSFs and trust with their impact on customer satisfaction.